Gene amplification of YB‐1 in castration‐resistant prostate cancer in association with aberrant androgen receptor expression. Issue 1 (24th November 2020) - Shiota, Masaki; Sekino, Yohei; Tsukahara, Shigehiro; Abe, Tatsuro; Kinoshita, Fumio; Imada, Kenjiro; Ueda, Shohei; Ushijima, Miho; Nagakawa, Shohei; Matsumoto, Takashi; Kashiwagi, Eiji; Takeuchi, Ario; et al.
Abstract: Although Y‐box binding protein‐1 (YB‐1) is known to be overexpressed in prostate cancer, especially castration‐resistant prostate cancer (CRPC), the mechanism of its overexpression remains unclear. We aimed to elucidate the mechanism of YB‐1 overexpression in CRPC. Gene amplification in CRPC cells and tissues was examined by public database analysis, and digital PCR. The significance of YB‐1 amplification for the YB‐1/androgen receptor (AR) axis and prognosis was examined by public database analysis and immunohistochemistry. YB‐1 amplification was mainly observed in CRPC tissues by public database analysis and confirmed in CRPC cells and tissues by digital PCR. Expression of YB‐1 was increased in CRPC tissues compared with treatment‐naïve tissues. Furthermore, YB‐1 and phosphorylated YB‐1 levels were associated with AR and AR V7 expression levels. Finally, YB‐1 amplification was associated with poor outcomes in CRPC. Taken together, the present findings suggest that YB‐1 amplification contributes to progression to CRPC through regulation of AR and AR V7 expressions, and that YB‐1 is a promising therapeutic target in CRPC. Abstract : Y‐box binding protein‐1 (YB‐1) amplification was observed in castration‐resistant prostate cancer (CRPC) and associated with an augmented androgen receptor signaling and poor prognosis. Taken together, the present findings suggest that YB‐1 amplification contributes to progression to CRPC, and that YB‐1 is a promising therapeutic target in CRPC.